PreEpiSeizures: description and outcomes of physiological data acquisition using wearable devices during video-EEG monitoring in people with epilepsy - Abreu, Mariana; Carmo, Ana Sofia; Peralta, Ana Rita; Sá, Francisca; Plácido da Silva, Hugo; Bentes, Carla; Fred, Ana Luísa (Frontiers in Physiology, 2023)
The PreEpiSeizures project was created to better understand epilepsy and seizures through wearable technology. The motivation was to capture physiological information related to epileptic seizures, besides electroencephalography during video-EEG monitorings. If other physiological signals have reliable information of epileptic seizures, unobtrusive wearable technology could be used to monitor epilepsy in daily life. The development of wearable solutions for epilepsy is limited to the nonexistence of datasets which could validate these solutions. 3 different form factors were developed and deployed, and the signal quality was assessed for all acquired biosignals. The wearable data acquisition was performed during the video-electroencephalography of patients with epilepsy. The results achieved so far include 59 patients, from 2 hospitals in a total of 2721 hours of wearable data and 348 seizures. Besides the wearable data, the ECG of the hospital is also usable, totalling 5838 hours of hospital data. The quality of the wearable electrocardiogram signal is equated with the hospital system, and all other biosignals also achieved state-of-the-art quality. During the data acquisition, 18 challenges were identified, and are presented alongside their possible solutions. Though this is an ongoing work, there were many lessons learned which could help to predict possible problems in wearable data collections and also contribute to the epilepsy community with new physiological information. This work contributes with original wearable data and results relevant to epilepsy research, and discusses relevant challenges that impact wearable health monitoring.